Spór i próba dialogu. O religijnej i laickiej narracji w życiu publicznym - Jocz, Artur (Polskie Towarzystwo Religioznawcze, 2014)
The aim of the remarks included here will be an attempt to track two kinds of narration which function in today’s public/scientific sphere. They are being led between intellectuals with a secular background and religiously engaged intellectuals, and those who in their remarks do not resign from the transcendent reality. So, there will be narrations considered related to the secular and religious interpretation of the Holocaust. Recalled will be also secular and religious readings of selected problems related to genetic engineering. The selection of such a diverse array of topics should serve for a better argumentation of the assumption saying that at the basis of religious and secular narration is situated a dynamic relation between faith and reason.
Keywords: religijność; wiara; racjonalizm; Holocaust; eugenika liberalna